Pengaruh Kepemimpinan Dan Spiritualitas Di Tempat Kerja Terhadap Kinerja Pegawai Melalui Semangat Kerja Pada Pegawai Kantor Bupati Deli Serdang - Ayu Juliani Siregar; Muis Fauzi Rambe (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to examine and analyze the influence of leadership and spirituality in the workplace on employee performance through the morale of the Deliserdang regent's office employees directly or indirectly. The approach used in this study is a causal approach. The population in this study were all employees of the Deliserdang regent's office. The sample in this study using the slovin formula totaling 52 employees of the Deliserdang regent's office. Data collection techniques in this study used questionnaire methode. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that leadership has a significant effect on performance directly, spirituality in the workplace has a significant effect on performance, direct morale has a significant effect on performance, direct leadership has a significant effect on morale, and spirituality in the workplace has a significant effect, on work morale indirectly work morale is able to mediate the influence of leadership onperformance, endirectly work morale is able to mediate the influence of spirituality in the workplace on the performance of the Deli Serdang regent’s office employee.